Optimization of Social Systems in the Diffusion of Innovations in Traditional Islamic Society: Study of Grameen Bank in Bangladesh - Charolin Indah; Abdul Hakim (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2023)
The diffusion of innovation in the context of developing traditional societies has its challenges with the many obstacles in the social system. Previous studies have proven that each social component has a significant role in facilitating the process of innovation diffusion to underprivileged societies. However, they need to discuss how to optimize these components to overcome the barriers of social systems in traditional societies. Meanwhile, M. Yunus created an innovation in the form of microcredit and successfully diffused it to Muslim women who live in poverty in Bangladesh. This study investigates how Yunus optimizes the social system's components to successfully diffuse the program's innovation in the high traditional challenges. The method used in this study is a qualitative approach with a type of case study and analysis based on Rogers' theory of social system components. This study finds that social system barriers can be overcome by 1) optimizing the role of reforming agents in optional decisions through interpersonal relationships; 2) optimizing local communication channels that are homophilous with friendship networks among lower-class Muslim women.